Explicit and implicit emotional expression in bulimia nervosa in the acute state and after recovery. - Salomé Tárrega (Public Library of Science (PLoS), 2014)
Expression of emotional state is considered to be a core facet of an individual's emotional competence. Emotional processing in BN has not been often studied and has not been considered from a broad perspective. This study aimed at examining the implicit and explicit emotional expression in BN patients, in the acute state and after recovery. Sixty-three female participants were included: 22 BN, 22 recovered BN (R-BN), and 19 healthy controls (HC). The clinical cases were drawn from consecutive admissions and diagnosed according to DSM-IV-TR diagnostic criteria. Self reported (explicit) emotional expression was measured with State-Trait Anger Expression Inventory-2, State-Trait Anxiety Inventory, and Symptom Check List-90 items-Revised. Emotional facial expression (implicit) was recorded by means of an integrated camera (by detecting Facial Feature Tracking), during a 20 minutes therapeutic video game. In the acute illness explicit emotional expression [anxiety (p<0.001) and anger (p<0.05)] was increased. In the recovered group this was decreased to an intermediate level between the acute illness and healthy controls [anxiety (p<0.001) and anger (p<0.05)]. In the implicit measurement of emotional expression patients with acute BN expressed more joy (p<0.001) and less anger (p<0.001) than both healthy controls and those in the recovered group. These findings suggest that there are differences in the implicit and explicit emotional processing in BN, which is significantly reduced after recovery, suggesting an improvement in emotional regulation.